INEFFICIENCY AND INSTITUTIONAL ISSUES IN THE PROVISION OF MERIT GOODS A Case Study of Public Water Supply in Rural Kerala - Santhakumar, V (Centre for Development Studies-WP285, 1998)
This paper discusses the issues of inefficiency in the provision of merit goods, taking the case of public water supply in rural Kerala. The analysis has identified two source of inefficiency in the provision of merit good. First, is due to the fact that the state and its agencies autonomously decide the nature and characteristics of the merit good. If the nature of good provided is not preferred by the people, or its consumption require effort on the part of citizens, these may lead to the non-consumption of the good by a large number of people. Thus, the definition of safe water as pipe water (from a centralised system) in the case of Kerala, lead to its effective non-use by a significant part of rural population. The second source of inefficiency in the provision of merit good, is in the selection of the institutional framework. The acquisition and free distribution of water by the state agency, is the prevailing institutional framework in Kerala, and this is inappropriate in efficiently solving the drinking water problem of different localities, taking their specific characteristics into account. The paper outlines a logical framework, which can be used to identify the necessary mechanism of government intervention in water supply in different localities.